Two examples of indication specific radiation dose calculations in dental CBCT and Multidetector CT scanners. (September 2017) - Stratis, Andreas; Zhang, Guozhi; Lopez-Rendon, Xochitl; Politis, Constantinus; Hermans, Robert; Jacobs, Reinhilde; Bogaerts, Ria; Shaheen, Eman; Bosmans, Hilde
Highlights: 3D dental CBCT scans for orthognathic treatment planning are dose wise justified. Orthognathic dental CBCT exposures deliver lower radiation doses compared to MSCTs. For temporal bone imaging protocols the two modalities deliver similar doses. Abstract: Purpose: To calculate organ doses and estimate the effective dose for justification purposes in patients undergoing orthognathic treatment planning purposes and temporal bone imaging in dental cone beam CT (CBCT) and Multidetector CT (MDCT) scanners. Methods: The radiation dose to the ICRP reference male voxel phantom was calculated for dedicated orthognathic treatment planning acquisitions via Monte Carlo simulations in two dental CBCT scanners, Promax 3D Max (Planmeca, FI) and NewTom VGi evo (QR s.r.l, IT) and in Somatom Definition Flash (Siemens, DE) MDCT scanner. For temporal bone imaging, radiation doses were calculated via MC simulations for a CBCT protocol in NewTom 5G (QR s.r.l, IT) and with the use of a software tool (CT-expo) for Somatom Force (Siemens, DE). All procedures had been optimized at the acceptance tests of the devices. Results: For orthognathic protocols, dental CBCT scanners deliver lower doses compared to MDCT scanners. The estimated effective dose (ED) was 0.32 mSv for a normal resolution operation mode in Promax 3D Max, 0.27 mSv in VGi-evo and 1.18 mSv in the Somatom Definition Flash. For temporal bone protocols, the Somatom Force resulted in an estimated ED of 0.28 mSv while for NewTom 5G the ED was 0.31 and 0.22 mSv for monolateral and bilateral imaging respectively. Conclusions: Two clinical exams which are carried out with both a CBCT or a MDCT scanner were compared in terms of radiation dose. Dental CBCT scanners deliver lower doses for orthognathic patients whereas for temporal bone procedures the doses were similar.